2018
DOI: 10.1248/cpb.c17-00922
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Thiophene, Thiazole and Coumarin Derivatives Based on Benzimidazole Nucleus and Their Cytotoxicity and Toxicity Evaluations

Abstract: The reactivity of compounds 2-(1-(2-chloroacetyl)-1H-benzo[d]imidazol-2-yl)acetonitrile 2 and 3-(1-(2-chloroacetyl)-1H-benzo[d]imidazol-2-yl)-2H-chromen-2-one 8 towards different chemical reagents were studied and a series of novel benzimidazole derivatives were obtained (2-6a-d and 8-12a-d). Moreover, in vitro growth inhibitory effect of the newly synthesized compounds were evaluated in term of [IC µM] against the six cancer cell lines, human lung carcinoma (A549), lung cancer (H460), human colorectal (HT29),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It has been found that many metal or metal oxide nanoparticles have many important applications as biologically active systems especially as antimicrobial agents 3542. We report herein as continuation to our interest in the design of bioactive heterocyclic compounds,4348 the preparation of novel dihydropyridinone disperse azo dyes derivatives with their SeNPs and their application as disperse dyes for the dyeing of nylon 66. The fastness properties and the antimicrobial activities of these dyes were also studied.…”
Section: Introductionmentioning
confidence: 79%
“…It has been found that many metal or metal oxide nanoparticles have many important applications as biologically active systems especially as antimicrobial agents 3542. We report herein as continuation to our interest in the design of bioactive heterocyclic compounds,4348 the preparation of novel dihydropyridinone disperse azo dyes derivatives with their SeNPs and their application as disperse dyes for the dyeing of nylon 66. The fastness properties and the antimicrobial activities of these dyes were also studied.…”
Section: Introductionmentioning
confidence: 79%
“…Procedure for toluene solution of 2,6-difluoro-3-nitrobenzoylchloride 3 was reported [8]. 2-Benzoylmethylbenzimidazole was prepared from 2-methylbenzimidazole [5], 2-cyanomethyl-benzimidazole was synthesized by condensation of ethyl cyanoacetate with o-phenylenediamine [10]. Thioamides 11 were prepared by the addition of hydrogen sulfide to the corresponding nitriles [11].…”
Section: Methodsmentioning
confidence: 99%
“…HH(45), 77 (71), 51(10).Found, %: C 60.03; H 2.83; N 12.20. С 23 H 13 FN 4 O 4 S. Calculated, %: C 60.00; H 2.85; N 12.17.…”
mentioning
confidence: 98%
“…The in vitro antitumor potency of a new series of benzimidazole-quinolinone derivatives was evaluated against HepG2, SKOV3, NCI-H460, and BEL-7404 cancer cell lines along with the toxicity of these molecules against the HL-7702 normal human liver cell line [179]. Novel N1, C2-substituted benzimidazoles were synthesized by Mohareb et al and screened against A549, H460, HT29, MKN-45, U87MG, and SMMC-7721 cancer cell lines [180]. The most potent compounds in this series exhibited IC 50 values in the range between 0.2-4.0 µM against all cancer cell lines tested, while compounds 202-206 were non-toxic when tested against shrimp larvae.…”
Section: Benzimidazole Containing and Related Moleculesmentioning
confidence: 99%